A systematic approach and mathematical review to textile production optimization: implementing lean six sigma DMAIC for enhanced product consistency and quality in the field of industrial engineering management - Chandan Chandra Sheel (Big Data and Computing Visions)
The main aim of this paper is to analyze the application of LSS tools to enhance efficiency and product quality within the region's textile sector. Specifically, the paper's objective is three-fold: to discuss how Lean and Six Sigma may be implemented separately, to discuss how these two improvement methodologies can be integrated, and to develop an integrated framework of Lean Six Sigma (LSS). The current research being conducted includes the use of journal articles and the use of the actual method. This gives an overview of previous frameworks and approaches to Lean and Six Sigma integration and establishes a new LSS Framework using DMAIC methodology. This study also comprises the quantitative and qualitative data collection from the survey and process evaluation in the Ready-Made Garment (RMG) factory. The research presented here outlines a comprehensive LSS strategy that would drastically cut down on defects and increase efficiency in the textile industry. According to the case, using LSS, the rework's Sigma level improved from 2.7 to 3.0, proving fewer defects. This paper introduces a novel  LSS framework tailored for the textile industry, especially Small and Medium-sized Enterprises (SMEs). Building on previous research, it identifies specific challenges faced by the textile sector and recommends adopting digital technologies and environmental considerations, including Green  LSS. The study offers valuable insights for practitioners aiming to implement continuous improvement approaches, particularly in SMEs, by integrating digital tools.